Rural residences of Wrocław burghers in the 13th-16th centuries - Dominik Nowakowski (Przegląd Archeologiczny)
The article discusses the issue of latemedieval and early-modern manor houses of Wrocław citizens, located in their rural properties. Many of them, located in the close vicinity of Wrocław, were destroyed as a result of the spatial development of the urban agglomeration, others are usually poorly researched archaeologically and architecturally. For this reason, and in accordance with the requirements of historical archaeology, this issue has been analyzed using a maximum variety of sources: written, archaeological, architectural, cartographic and iconographic. The article includes examples of manor houses built by the citizens of Wrocław as well as those that originally belonged to dukes or knights. The key issues to which special attention has been given are the chronology and formal classification of objects as well as their functions and significance for their founders and owners. The issue was discussed in four chronological intervals, basically reflecting the economic, social and political changes that influenced the development of Silesian defensive-residential buildings.